2011
DOI: 10.1111/j.1365-2621.2011.02881.x
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleiferia leaves extract: a natural antioxidant for retarding lipid peroxidation in cooked goat meat patties

Abstract: The effective utilisation of Moringa oleiferia mature leaves (MOL) extract as an antioxidant in cooked goat meat patties during refrigerated storage was investigated, and its efficiency was evaluated against butylated hydroxytoluene (BHT). The extract exhibited high phenolic content (48.36 mg of gallic acid equivalent per g), flavonoid (31.42 mg g )1 of sample) being the major component. Moringa oleiferia mature leaves extract showed excellent antioxidant activity as determined by radical-scavenging activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
84
1
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 33 publications
14
84
1
16
Order By: Relevance
“…The results of the proximate composition indicated that MLP had a high protein content (293.7 g/kg) with considerable amounts of crude fiber (94.2 g/kg), ash (87.5 g/kg), moisture (82.8 g/ kg), fat (70.0 g/kg), total phenolics (2010.3 mg GAE/kg), and flavonoids (48.0 mg CE/kg). These findings are slightly different from those reported previously for moringa leaves of different origin (Das, Rajkumar, Verma, & Swarup, 2012;Moyo, Masika, Hugo, & Muchenje, 2011;Shah et al, 2015). Although the observed differences in chemical composition of moringa leaves between these studies are minor, they could be attributed to the variation in the environmental conditions, mainly temperature and soil fertility, agronomic practices such as irrigation, fertilization, harvest, and postharvest and extraction conditions (methods and solvents) and the maturity stage of moringa leaves.…”
Section: Chemical Composition and Antimicrobial Activity Of Mlpcontrasting
confidence: 93%
See 2 more Smart Citations
“…The results of the proximate composition indicated that MLP had a high protein content (293.7 g/kg) with considerable amounts of crude fiber (94.2 g/kg), ash (87.5 g/kg), moisture (82.8 g/ kg), fat (70.0 g/kg), total phenolics (2010.3 mg GAE/kg), and flavonoids (48.0 mg CE/kg). These findings are slightly different from those reported previously for moringa leaves of different origin (Das, Rajkumar, Verma, & Swarup, 2012;Moyo, Masika, Hugo, & Muchenje, 2011;Shah et al, 2015). Although the observed differences in chemical composition of moringa leaves between these studies are minor, they could be attributed to the variation in the environmental conditions, mainly temperature and soil fertility, agronomic practices such as irrigation, fertilization, harvest, and postharvest and extraction conditions (methods and solvents) and the maturity stage of moringa leaves.…”
Section: Chemical Composition and Antimicrobial Activity Of Mlpcontrasting
confidence: 93%
“…Reduction of peroxide values may be due to inhibition of lipid peroxidation by MLP, which contains polyphenols and flavonoids, which have antioxidant effects (Jayawardana et al, 2015). Similarly, several reports revealed that incorporation of moringa leaf and seed extracts in meat products significantly inhibited lipid oxidation (Al-Juhaimi et al, 2016a;Das et al, 2012;Muthukumar et al, 2014;Shah et al, 2015). From the results of the present study, total phenols and flavonoids of MLP have antioxidant activity, which could have led to the observed peroxide value reduction of chicken patties during the storage period.…”
Section: Effect Of Mlp On Ph and Peroxide Values Of Chicken Pattiessupporting
confidence: 71%
See 1 more Smart Citation
“…Das et al (2012) reported the total phenolics of aqueous extract of MLE were 48.36 mg GAE/g. while according to Sreelatha and Padma (2009), the total phenolics of MLE were 45.81 mg GAE/g Since polyphenols are responsible for the antioxidant activity, the high phenolic content in the MLE indicates its high antioxidant activity.…”
Section: Antioxidant Properties Of M Oleifera Leaf Extractmentioning
confidence: 98%
“…M. oleifera leaves have been used to extend the shelf life of ghee as these leaves are rich in several types of natural antioxidant compounds such as ascorbic acid, carotenoids and phenolic substances (Siddhuraju & Becker, 2003). M. oleifera leaf extract (MLE) showed antioxidant properties as revealed by the following determinations: the Total Antioxidant Activity (TAA), 2,2-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging activity and reducing power (Sreelatha & Padma, 2009), MLE was used as a natural preservative in goat meat patties (Das, Rajkumar, Verma, & Swarup, 2012) and pork patties (Muthukumar et al, 2012). The objective of this paper was to investigate the effect of M. oleifera leaf extract on physicochemical properties of modified atmospheric packaged raw beef stored at refrigerated temperature.…”
Section: Introductionmentioning
confidence: 99%